Insider Trading as a Signal of Private Information - Damodaran, Aswath; Liu, Crocker H. (Review of Financial Studies, 1993)
There is substantial evidence that insider trading is present around corporate announcements and that this insider trading is motivated by private information. Using real estate investment trusts that choose to reappraise themselves as our sample, we establish that the appraisals contain information, but find no market response to the public announcement of this information in these appraisals. We consider two possible explanations for this inconsistency: the first that the appraisal information is not highlighted in earnings reports and hence remains unobserved; and the second that insiders trade on the appraisal information in the time that elapses between the appraisal and its public announcement. We find strong support for the second hypothesis, with insiders buying (selling) after they receive favorable (unfavorable) appraisal news, especially for negative appraisals. We also find that positive (negative) appraisals and net insider buying (selling) elicit significant positive (negative) abnormal returns during the appraisal period.